2021
DOI: 10.1021/acsami.0c19977
|View full text |Cite
|
Sign up to set email alerts
|

Highly Multifunctional and Thermoconductive Performances of Densely Filled Boron Nitride Nanosheets/Epoxy Resin Bulk Composites

Abstract: In the development of hexagonal boron nitride (h-BN)-based polymeric composites with high thermal conductivity, it is always challenging to achieve a dense filling of h-BN fillers to form a desired high-density thermal transfer network. Here, a series of boron nitride nanosheets (BNNSs)/epoxy resin (EP) bulk composites filled with ultrahigh BNNSs content (65−95 wt %) is successfully constructed through a well-designed mechanical-balling prereaction combined with a general pressure molding method. By means of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 75 publications
3
39
0
Order By: Relevance
“…The mPS nanoparticles are successfully anchored and immobilized on the BN-OH nanosheets, implying the existence of some interactions including hydrogen bonding interaction πÀπ stacking and van der Waals interactions. [34,40] In particular, when the amount of BN-OH@mPS is 6 wt%, mPS is uniformly distributed on the BN-OH as observed from the SEM image in Figure 3C,D, which is also confirmed by B and C elemental mapping images (Figure 3E,F). It can be found that BN-OH nanosheets are linked to each other, and the BN-OH nanosheets were tightly wrapped by PS nanoparticles forming core-shell structures.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The mPS nanoparticles are successfully anchored and immobilized on the BN-OH nanosheets, implying the existence of some interactions including hydrogen bonding interaction πÀπ stacking and van der Waals interactions. [34,40] In particular, when the amount of BN-OH@mPS is 6 wt%, mPS is uniformly distributed on the BN-OH as observed from the SEM image in Figure 3C,D, which is also confirmed by B and C elemental mapping images (Figure 3E,F). It can be found that BN-OH nanosheets are linked to each other, and the BN-OH nanosheets were tightly wrapped by PS nanoparticles forming core-shell structures.…”
Section: Resultssupporting
confidence: 65%
“…[32] Compared to the pristine BN, the peak position of the (002) plane of BN-OH has a left shift from 26.90 to 26.64 , which is attributed to the increase of interplanar distance during exfoliation. [34] Besides, the full width at half maxima (FWHM) of the (002) peak of BN-OH is larger than that of BN, revealing that the thickness of the layer becomes thinner. [35] The typical exfoliation and functionalization schematics are displayed in Figure 2G.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the temperature increasing, the thermal conductivities of the composites in both the inplane and out-of-plane directions were reduced, but remained high (in-plane: over 20 W/mK; out-of-plane: over 1.7 W/mK) until 150 C. This shows that the HPF-BNNSs/PVA composites can maintain an excellent heatdissipating function under high temperatures. Compared with other BN-based polymer composites in previous studies (Figure 4f), [37][38][39][40][41][42][43][44][45] our composite exhibited a relatively high thermal conductivity at medium filler loading, and our fabrication method is preferable to those in earlier works, which used complicated procedures and toxic materials.…”
Section: Thermal Properties Of the Compositesmentioning
confidence: 74%
“…Thermally conductive but insulating llers such as Al 2 O 3 have low CLTE ($6.6 ppm/ C), 27 which can meet the performance requirements of high thermal conductivity and low CLTE of silicone potting adhesive under the condition of large amount of lling. For example, Fu et al 28 prepared a series of dense boric acid modied BNNSs/EP composites by mechanical ball milling and pressure forming processes; the EP composites with 90 wt% BNNSs achieved the maximum thermal conductivity (6.7 W m À1 k À1 ) and the minimum CLTE (4.5 ppm/ C) at a temperature of 25 C. Unfortunately, high ller loading will inevitably cause a sharp increase in the viscosity of silicone potting adhesive, which makes it impossible to achieve potting under mechanical or articial conditions. 29 In this study, Al 2 O 3 -epoxy and Al 2 O 3 -NH 2 powders were equally lled in vinyl silicone oil to prepare a high Al 2 O 3 loading (89 wt%) precursor of silicone potting adhesive.…”
Section: Introductionmentioning
confidence: 99%